Epidemiologia e previsão da mancha bacteriana (Xanthomonas spp.) do tomateiro - Marcuzzo, Leandro Luiz (2008)
Experiments were carried out in Caçador-SC, Brazil, to explore some epidemic characteristics and to develop a forecasting model for the tomato bacterial spot caused by Xanthomonas spp. During 19 weeks, epidemiological studies were carried by weekly monitoring the epiphytic bacterial population, severity, and by recording the prevalent weather conditions. For the forecasting system developed under climatized chambers in the field, different severity levels of the disease were compared to the conventional spraying system. The following spraying regimes were used: 1) Based on the forecast model SE with severity threshold (SE) of 0.05; 2) Based on the forecast model with severity threshold (SE) of 0.15; 3) Based on the forecast model with severity threshold (SE) of 0.25; 4) Conventional spraying regime with five day interval and 5) Conventional spraying regime with seven day interval. Data were adjusted to Gompertz nonlinear regression model (y = ymax * (exp (-ln (yo / ymax) * exp (-r * x))). Daily weather records were registered during the crop season. It was observed that epidemic onset coincided with physiological maturation of the first cluster of fruits. The disease curve progress was fitted to the logistic model y = 0,99964/(1+exp(10.35989-0.69762*x)), where Y is disease severity and x the time in days. Severity in fruits reaching 30.22% with total productivity of 117.88 ton.ha-1. The area under disease progress curve (AUDPC) was reduced in 25.71% for SE = 0.15 with the same number of spraying carried through weekly. This was not different from SE = 0.05. In the treatment 3 (SE = 0.25) the number of sprays was 54.1% and 35.3% less compared to five day and seven day spray regime, respectively and the corresponding AUDPC were 9.83% and 19.66%. The forecasting model with severity threshold SE = 0.15 and 0.25 showed advantages in relation to the conventional spraying regime